Sclerosing mucoepidermoid carcinoma of minor salivary gland - Lohiya, Pooja G. (Contemp Clin Dent, 2014)
Sclerosing mucoepidermoid carcinoma (SMEC) is extremely rare variant of the mucoepidermoid carcinoma, which is the most common primary malignancy of the salivary glands. As its name suggests, SMEC is characterized by an intense central sclerosis that occupies the entirety of an otherwise typical tumor, frequently with an inflammatory infiltrate of plasma cells, eosinophils, and/or lymphocytes at its peripheral regions, but its uncompanionship with inflammatory cell infiltration might explain its progressive stage of the sclerosis. The sclerosis associated with these tumors may obscure their typical morphologic features and result in diagnostic difficulties. Tumor infarction and extravasation of mucin eventuating in reactive fibrosis are two mechanisms of formation that have been suggested as underlying this morphologic variant. Morphologic evidence in support of the mucin extravasation hypothesis was identified, as small pools of mucin were present throughout the tumor.